A Cu-Zr / SiO2 catalyst and its preparation method and its application in one-step ethanol to butadiene reaction
The Cu-Zr/SiO2 catalyst prepared by using silica sol and post-ammonia distillation strategy in the one-step butadiene process of ethanol production was solved, and high-efficiency and low-cost butadiene preparation was achieved.
Patent Information
- Application Number
- CN202211567785.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-07
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2042-12-07
AI Technical Summary
The existing one-step ethanol process is poor in the stability of butadiene catalyst, and the preparation process of molecular sieve support is complex and expensive.
The cheap and easy-to-get silicon sol is used as the silicon source, and the active components are introduced through the strategy of ammonia distillation and post-impregnation to construct the Cu-Zr-Si interface, promote the synergistic effect of ethanol dehydrogenation and subsequent reactions, and prepare the Cu-Zr/SiO2 catalyst.
It realizes high efficiency, high selectivity and high yield conversion of ethanol into butadiene. The catalyst has high reaction stability, low cost, simple process, and easy to industrial application.
Smart Images

Figure CN116196924B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a Cu-Zr / SiO2 catalyst and a preparation method thereof and application thereof in a one-step ethanol-to-butadiene reaction, belonging to the technical field of a one-step ethanol-to-butadiene reaction. Background Art
[0002] 1,3-Butadiene (hereinafter referred to as butadiene) is an important basic organic chemical raw material, mainly used in the production of synthetic rubber and synthetic resin, etc., and has a wide range of uses. The annual global production of butadiene exceeds 16 million tons, which is mainly obtained by separating the by-products of naphtha cracking to produce ethylene. Therefore, its production not only depends on non-renewable petroleum resources, but also is restricted by the production scale of petroleum ethylene [Makshina, EV; Dusselier, M.; Janssens, W.; Degreve, J.; Jacobs, PA; Sels, BF, Review of old chemistry and new catalytic advances in the on-purpose synthesis of butadiene. Chem. Soc. Rev., 2014, 43, 7917-7953.]. In recent years, the large-scale application of shale gas technology in the world has led to a substantial increase in the production capacity of ethane dehydrogenation to ethylene [Gao, Y.; Neal, L.; Ding, D.; Wu, W.; Baroi, C.; Gaffney, AM; Li, F., Recent advances in intensified ethylene production-A review. ACS Catal., 2019, 9, 8592-8621.]; in my country, the annual output of methanol to olefins has reached one-third of petroleum olefins [Tian, P.; Wei, Y.; Ye, M.; Liu, Z., Methanol to olefins (MTO): From fundamentals to commercialization. ACS Catal., 2015, 5, 1922-1938.]. The diversification of ethylene sources has reduced the market demand for naphtha cracking technology, which in turn limits the future increase in butadiene production capacity. Therefore, the development of new butadiene preparation technologies, especially those based on renewable raw materials, is of great significance to meet and ensure the growing demand for important bulk chemical products [Pomalaza, G.; Arango Ponton, P.; Capron, M.; Dumeignil, F., Ethanol-to-butadiene: the reaction and its catalysts. Catal. Sci. Techn., 2020, 10, 4860-4911.].
[0003] Ethanol is a clean fuel and can also be used as a raw material for catalytic conversion to produce butadiene, reducing dependence on and consumption of petroleum resources and promoting sustainable economic development. The rapid development of biotechnology worldwide in the past two decades has driven the cost of bioethanol down and the output up [Pang, J.; Zheng, M.; Zhang, T., Chapter Two-Synthesis of ethanol and its catalytic conversion. In Adv. Catal., 2019, 64, 89-191.]. In my country, the technology of synthesizing ethanol from syngas has been successfully applied commercially, and it has opened up a broad space for the development of ethanol as a cheap industrial raw material [Wen Yanjie, Coal-based ethanol technology innovation, Journal of the Chinese Academy of Sciences, 2019, 34, 724-725]. Against this background, the technology of catalytic conversion of ethanol to butadiene has a chance of revival.
[0004] The reaction of ethanol to butadiene is a green and sustainable process. Since 2011, the number of international research reports on ethanol to butadiene has gradually increased, and great progress has been made. Most of them have achieved excellent catalytic performance around supported zeolite catalysts, such as Zn-Y / Beat, LiZnHf-MFI (NS) and Zn-Ta-TUD-1. However, a common problem is that the stability of the catalyst prepared by the one-step method of ethanol is poor, and the preparation process of the constructed zeolite carriers is mostly complicated and the cost of organic templates is expensive. Summary of the invention
[0005] In order to solve the problem of complex molecular sieve preparation process and high cost, the present invention adopts cheap and easily available silica sol as the silicon source, introduces active components through the strategy of ammonia evaporation and post-impregnation, and the Cu-Zr-Si interface constructed by this method can promote the synergistic effect of ethanol dehydrogenation and subsequent aldol condensation and MPVO reduction, thereby realizing the efficient, high selectivity and high yield conversion of ethanol into butadiene. The constructed Cu-Zr-Si interface makes the catalyst have higher reaction stability.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] On one hand, the present invention provides a Cu-Zr / SiO2 catalyst, wherein the catalyst uses Cu and Zr as active components, and the loading amounts of the active components copper and zirconium in the catalyst are 0.5-40wt% and 1-30wt% respectively; the carrier is formed by stacking silicon dioxide nanospheres.
[0008] In the above technical solution, further, the diameter of the silica nanospheres is 20-30 nm, and the diameter of the accumulated mesopores is 2-20 nm.
[0009] In the above technical solution, further, the loading amount of the active component copper element in the catalyst is 1-20wt%, and the loading amount of the zirconium element in the catalyst is 2-25wt%.
[0010] Another aspect of the present invention provides a method for preparing the above-mentioned catalyst, the method comprising the following steps:
[0011] (1) stirring a soluble salt solution of Cu and a 25 wt% ammonia solution for 30 minutes, then adding silica sol and stirring for 1-6 hours;
[0012] (2) heating the mixed solution obtained in step (1) to 50-150° C. and treating with ammonia for 8-24 hours, gradually volatilizing the ammonia in the solution until the pH value of the solution reaches neutral, washing and filtering, drying at 60-200° C., and calcining in an air atmosphere at a calcination temperature of 300-800° C. for 1-9 hours to obtain Cu-SiO2;
[0013] (3) impregnating a soluble salt solution of Zr on Cu-SiO2, drying it at 60-200°C, and then calcining it in an air atmosphere at a calcination temperature of 300-800°C for 1-9 hours to obtain the catalyst Cu-Zr / SiO2.
[0014] In the above technical scheme, further, in the step (1), the soluble salt solution of Cu is one or more of copper nitrate, copper chloride, copper sulfate, copper acetate, and copper acetylacetonate; the molar ratio of copper to ammonia water is 1:10; and the particle size of the silica sol colloidal particles is 10-50 nm.
[0015] In the above technical solution, further, in the step (2), the temperature of the ammonia evaporation process is 80-120°C; the drying temperature is 100-120°C; the roasting temperature is 400-500°C, and the roasting time is 4-6 hours.
[0016] In the above technical solution, further, in the step (3), the soluble salt of Zr is one or more of zirconium nitrate, zirconium chloride, zirconium oxynitrate, zirconium oxychloride, and zirconium n-propoxide.
[0017] In another aspect, the present invention provides an application of the above catalyst in the one-step process of preparing butadiene from ethanol, wherein the reaction is carried out in a fixed bed reactor at atmospheric pressure, and the reaction space velocity is WHSV=0.2-10h -1 , preferably WHSV = 0.5-5h -1 , using at least one of nitrogen, helium and argon as carrier gas, carrier gas space velocity GHSV = 500-50000h -1 , preferably GHSV = 2000-20000h -1, the reaction temperature is 200-450°C, preferably 275-375°C.
[0018] The beneficial effects of the present invention are:
[0019] (1) The active components are cheap metal copper and zirconium. Compared with active component catalysts such as Ag, Ta, Hf and Y, the cost is lower and the industrialization prospect is more prominent.
[0020] (2) Compared with catalysts supported by molecular sieves, silica sol as a silicon-based carrier has lower cost and a simpler preparation process, making it easier to prepare in batches.
[0021] (3) The rich external surface area of the catalyst facilitates the mass transfer and diffusion of reactants, effectively increasing the ability to resist carbon deposition and improving the stability of the catalyst reaction. Compared with the reported Zr-based molecular sieve catalysts such as Ag-Zr / SiO2, Ag-Zr / Beta and Zn-Zr / SiO2, it has higher stability.
[0022] (4) The Cu-Zr / SiO2 catalyst has high yield and butadiene selectivity in the one-step process of ethanol to butadiene. Under the optimized reaction conditions, the butadiene selectivity can reach 85% and maintain high activity. Taking the above factors into consideration, the catalyst of the present invention has a good application prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The XRD pattern of the catalyst X%Cu-8%Zr / SiO2 prepared in Example 1;
[0024] Figure 2 This is the N2-physical adsorption diagram of the catalyst X%Cu-8%Zr / SiO2 prepared in Example 1;
[0025] Figure 3 TEM and element distribution diagram of the catalyst 2%Cu-8%Zr / SiO2 prepared in Example 1, wherein a is the TEM diagram and b is the element distribution diagram;
[0026] Figure 4 The stability test results of the catalyst 2%Cu-8%Zr / SiO2 prepared in Example 1;
[0027] Figure 5 The stability test results of the catalyst 2%Cu-8%Zr / MFI prepared in Comparative Example 1 are as follows;
[0028] Figure 6 These are the stability test results of the catalyst 2%Cu-8%Zr / Beta prepared in Comparative Example 2. DETAILED DESCRIPTION
[0029] The following is further detailed description through specific embodiments.
[0030] Example 1
[0031] (1) Preparation of X% Cu-SiO2 catalysts with different loading amounts by ammonia evaporation method:
[0032] Step A, dissolving 0.76g of copper nitrate in 7.6g of ammonia water, the mass ratio of copper to ammonia water being 1:10, stirring for 30 minutes, adding 12.5g of 40wt% silica sol solution (LUDOX, colloidal particle size being 10-50nm) and reacting for 4h, then transferring to a 80°C water bath for treatment for 12h, filtering and washing when the reaction solution has a pH of 7, and drying at 100°C for 8h to obtain 2% Cu-SiO2, and preparing other Cu loadings of 0.5%, 1%, 5%, 10%, and 20% by changing the amount of copper nitrate and ammonia water in accordance with the mass ratio of copper to ammonia water;
[0033] Step B, calcining the sample in step A at 400°C in air for 4 hours to obtain catalysts with different loading amounts of 0.5% Cu-SiO2, 1% Cu-SiO2, 2% Cu-SiO2, 5% Cu-SiO2, 10% Cu-SiO2, and 20% Cu-SiO2.
[0034] (2) Preparation of X%Cu-Y%Zr / SiO2 catalysts with different copper and zirconium loadings:
[0035] Zirconium nitrate was dissolved in water and impregnated with the above-mentioned X% Cu-SiO2 samples with equal volumes. The Zr loading was selected as 1%, 4%, 8%, 16%, and 24%, respectively. The mixture was dried at 100°C for 8 hours and calcined in air at 500°C for 4 hours to obtain copper-zirconium catalysts with different loadings.
[0036] The physical structure of the Cu-Zr / SiO2 catalyst was investigated by XRD, N2-physical adsorption, TEM and element distribution, further revealing the superiority of the porous molecular sieve catalyst constructed by ammonia evaporation and post-impregnation strategy.
[0037] The XRD pattern of X%Cu-8%Zr / SiO2 of Example 1 is as follows: Figure 1 As shown, the N2-physical adsorption diagram is as follows Figure 2 The pore structure properties of X%Cu-8%Zr / SiO2 are shown in Table 1; the TEM image and mapping image of 2%Cu-8%Zr / SiO2 are further shown in Figure 3 shown.
[0038] Table 1
[0039]
[0040] XRD results show that there are no CuO and ZrO2 particles, indicating that Cu and Zr are highly dispersed on the surface of silica, which is consistent with the electron microscopy mapping. TEM results show that the size of silica spheres is 20-30nm. Combined with the physical adsorption results, the mesopores mainly come from the accumulation of 20-30nm silica spheres.
[0041] Example 2
[0042] Preparation of X%Cu-Y%Zr / SiO2 at different calcination temperatures: The preparation process is similar to that of Example 1, except that the calcination temperatures are 500°C, 600°C, 700°C, and 800°C, respectively.
[0043] Comparative Example 1
[0044] The preparation method of the catalyst 2%Cu-8%Zr / MFI is as follows: 0.75g of copper nitrate is dissolved in water, and 100g of 25wt% ammonia water is added and stirred for 30 minutes, then 5g of MFI molecular sieve is added, stirred for 4h and then heated to 80°C for 12h, and when the pH of the reaction liquid is 7, it is filtered and washed, and dried at 100°C for 8h to obtain 2%Cu-MFI; 0.4g of zirconium nitrate is dissolved in 1g of water, impregnated with the above-mentioned 2%Cu-MFI catalyst in equal volume, dried at 100°C for 8h, and calcined in air at 500°C for 4h to obtain the catalyst 2%Cu-8%Zr / MFI.
[0045] Comparative Example 2
[0046] The preparation method of the catalyst 2%Cu-8%Zr / Beta is as follows: 0.75g of copper nitrate is dissolved in water, and 100g of 25wt% ammonia water is added and stirred for 30 minutes, followed by adding 5g of dealuminated Beta, stirring for 4h and then heating to 80°C for 12h, filtering and washing when the pH of the reaction liquid is 7, and drying at 100°C for 8h to obtain 2%Cu-Beta; 0.4g of zirconium nitrate is dissolved in 1g of water, impregnated with an equal volume of the above-mentioned 2%Cu-Beta catalyst, dried at 100°C for 8h, and calcined in air at 500°C for 4h to obtain the catalyst 2%Cu-8%Zr / Beta.
[0047] Comparative Example 3
[0048] The 2%Cu / 8%Zr / SiO2 catalyst was prepared by the impregnation method. Copper nitrate was dissolved in water and impregnated with an equal volume of a commercially available silica carrier with a Cu loading of 2%. The catalyst was dried at 100°C for 8 hours and then calcined in air at 400°C for 4 hours to obtain a 2%Cu / SiO2 catalyst. Zirconium nitrate was then dissolved in water and impregnated with an equal volume of the 2%Cu / SiO2 carrier with a Zr loading of 8%. The catalyst was dried at 100°C for 8 hours and then calcined in air at 400°C for 4 hours to obtain a 2%Cu / 8%Zr / SiO2 catalyst.
[0049] Comparative Example 4
[0050] A 2% Cu / 8% Zr / SiO2 (co-impregnation) catalyst was prepared by co-impregnation. Copper nitrate and zirconium nitrate were dissolved in water and impregnated with an equal volume of a commercially available silica carrier. The Cu loading was 2% and the Zr loading was 8%. The catalyst was dried at 100°C for 8 hours and then calcined in air at 400°C for 4 hours to obtain a 2% Cu / 8% Zr / SiO2 (co-impregnation) catalyst.
[0051] Comparative Example 5
[0052] The catalyst 2% Cu-SiO2+8% Zr / SiO2 was prepared by mechanical mixing: the carrier SiO2 was first impregnated with Zr and evaporated ammonia Cu to obtain Cu-SiO2 and 8% Zr / SiO2, and then ground for 30 minutes to obtain the catalyst 2% Cu-SiO2+8% Zr / SiO2.
[0053] Test Example 1
[0054] Catalyst evaluation process for one-step preparation of butadiene from ethanol: 0.5 g of the catalyst prepared in Example 1 was pelletized and loaded into a fixed bed reactor. The raw material was brought into the reactor by pump feeding and carrier gas (flow rate of 100 mL / min). The reaction space velocity was WHSV = 0.96 h -1 , the reaction temperature is 350℃.
[0055] Reaction conversion and selectivity calculation method:
[0056] Ethanol conversion rate (%) = (n 反应前的乙醇 -n 反应后剩余乙醇 ) / n 反应前的乙醇 *100%
[0057] Butadiene selectivity (%) = 2n 产物中丁二烯 / (n 反应前的乙醇 -n 反应后剩余乙醇 )*100%
[0058] The performance of 2%Cu-Y%Zr / SiO2 catalysts with different zirconium loadings was evaluated, and the reaction results are shown in Table 2.
[0059] Table 2
[0060]
[0061]
[0062] It can be seen from the table that when the Zr loading is 1-24%, it has relatively good catalytic performance, and the loading of 8% is the most outstanding.
[0063] Test Example 2
[0064] The performance of the Cu-Zr / SiO2 catalyst with different copper and zirconium loadings in Example 1 was further evaluated, and the reaction conditions were the same as those in Test Example 1.
[0065] Table 3
[0066] catalyst Ethanol conversion rate (%) Butadiene selectivity (%) <![CDATA[1%Cu-4%Zr / SiO2]]> 75 43 <![CDATA[1%Cu-8%Zr / SiO2]]> 78 45 <![CDATA[1%Cu-16%Zr / SiO2]]> 80 46 <![CDATA[5%Cu-4%Zr / SiO2]]> 86 45 <![CDATA[5%Cu-8%Zr / SiO2]]> 89 50 <![CDATA[5%Cu-16%Zr / SiO2]]> 93 47 <![CDATA[20%Cu-4%Zr / SiO2]]> 98 43 <![CDATA[20%Cu-8%Zr / SiO2]]> 96 51 <![CDATA[20%Cu-16%Zr / SiO2]]> 95 49
[0067] It can be seen from the table that the loading amounts of Cu and Zr are in the range of 1-20% and 4-16%, respectively, which can realize the conversion of ethanol into butadiene and have good catalytic performance.
[0068] Test Example 3
[0069] In Test Example 1, the optimal Zr loading was preferably 8%, and the performance of the X%Cu-8%Zr / SiO2 catalyst with different Cu loadings in Example 1 was evaluated. The reaction conditions were the same as in Test Example 1.
[0070] Table 4
[0071]
[0072]
[0073] It can be seen from the table that for the Cu-Zr / SiO2 catalyst, good catalytic performance can be achieved, and the catalyst 2%Cu-8%Zr / SiO2 shows the best butadiene selectivity.
[0074] Test Example 4
[0075] The catalytic performance of 2%Cu-8%Zr / SiO2 was investigated at different calcination temperatures, and the reaction conditions were the same as those in Test Example 1.
[0076] Table 5
[0077] Calcination temperature (℃) Ethanol conversion rate (%) Butadiene selectivity (%) 400 80 81 500 83 85 600 72 65 700 65 53 800 60 42
[0078] It can be seen from the table that the catalyst provided by the present invention can stably exist and produce the target product acetaldehyde under the condition of a calcination temperature of 400-800°C, and the optimal calcination temperature for the reaction is 500°C.
[0079] Test Example 5
[0080] The catalytic performance of 2%Cu-8%Zr / SiO2 catalyst at different reaction temperatures was investigated, and the other reaction conditions were the same as those in Test Example 1.
[0081] Table 6
[0082] Reaction temperature (℃) Ethanol conversion rate (%) Butadiene selectivity (%) 250 0 0 275 57 76 300 71 78 325 83 85 350 92 87 400 100 62
[0083] It can be seen from the table that the catalyst provided by the present invention can produce the target product butadiene under the reaction conditions of 275-400°C, and the optimal reaction temperature is 325°C.
[0084] Test Example 6
[0085] Comparison of catalyst stability:
[0086] In order to further highlight the superiority of the present invention, the stability of the catalyst 2% Cu-8% Zr / SiO2 was investigated, and the stability of the catalyst 2% Cu-8% Zr / MFI of Comparative Example 1 and the catalyst 2% Cu-8% Zr / Beta of Comparative Example 2 were compared. WHSV = 0.64h -1 , other conditions are the same as those in test example 1. The test results are as follows Figure 4-6 As shown in the figure, it can be seen that the catalyst of the present invention can operate stably within 80 hours, which is better than the copper-zirconium catalyst of MFI and Beta molecular sieve.
[0087] Test Example 7
[0088] In order to further highlight the superiority of the present invention, the catalytic performance of the catalyst 2% Cu-8% Zr / SiO2 is compared with that of Comparative Example 3, Comparative Example 4 and Comparative Example 5, and the reaction conditions are consistent with those of Test Example 1.
[0089] Table 7
[0090] catalyst Ethanol conversion rate (%) Butadiene selectivity (%) <![CDATA[2%Cu-8%Zr / SiO2]]> 83 85 <![CDATA[2%Cu / 8%Zr / SiO2]]> 62 58 <![CDATA[2% Cu / 8% Zr / SiO2 (co-impregnation)]]> 57 61 <![CDATA[2%Cu-SiO2+8%Zr / SiO2]]> 55 49
[0091] From the results in the table, it can be seen that the catalytic effect of the catalyst 2% Cu-8% Zr / SiO2 in the reaction is significantly better than that of the catalysts prepared by the impregnation method and mechanical mixing, which indicates the high ethanol conversion rate and butadiene selectivity of the present invention.
[0092] In summary, the present invention prepares a dual-site 2% Cu-8% Zr / SiO2 catalyst based on the ammonia evaporation-post-impregnation strategy, which can be used for the one-step production of butadiene from ethanol. The catalyst prepared by this strategy has the advantages of high conversion rate, high butadiene selectivity, high reaction stability, simple preparation process, low cost, etc., and can also be mass-produced and easy to industrially apply.
Claims
1. A Cu-Zr / SiO2 catalyst, characterized in that: The catalyst has Cu and Zr as active components, and the loading amounts of active components copper and zirconium in the catalyst are 0.5-40 wt% and 1-30 wt% respectively; the carrier is formed by stacking of silicon dioxide nanospheres; The preparation method of the catalyst comprises the following steps: (1) Stir the soluble salt solution of Cu and 25wt% ammonia solution for 30 minutes, then add silica sol and stir for 1-6 hours; (2) The mixed solution obtained in step (1) is heated to 50-150 o C ammonia evaporation treatment for 8-24 h, gradually volatilize the ammonia in the solution until the pH value of the solution reaches neutral, wash and filter, and then pass through 60-200 o After drying at 300-800 °C, the sintered product is calcined in air. o C, calcination time is 1-9 hours to obtain Cu-SiO2; (3) Impregnate the soluble salt solution of Zr on Cu-SiO2 for 60-200 o After drying at 300-800 °C, the sintered product is calcined in air. o C, the calcination time is 1-9 hours to obtain the catalyst Cu-Zr / SiO2.
2. The catalyst according to claim 1, characterized in that: The diameter of the silicon dioxide nanospheres is 20-30 nm, and the diameter of the accumulated mesopores is 2-20 nm.
3. The catalyst according to claim 1, characterized in that: The active component copper element is loaded in the catalyst in an amount of 1-20wt%, and the active component zirconium element is loaded in the catalyst in an amount of 2-25wt%.
4. A method for preparing the catalyst according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: (1) Stir the soluble salt solution of Cu and 25wt% ammonia solution for 30 minutes, then add silica sol and stir for 1-6 hours; (2) The mixed solution obtained in step (1) is heated to 50-150 o C ammonia evaporation treatment for 8-24h, gradually volatilize the ammonia in the solution until the pH value of the solution reaches neutral, wash and filter, and pass through 60-200 o After drying at 300-800 °C, the sintered product is calcined in air. o C, calcination time is 1-9 hours to obtain Cu-SiO2; (3) Impregnate the soluble salt solution of Zr on Cu-SiO2 for 60-200 o After drying at 300-800 °C, the sintered product is calcined in air. o C, the calcination time is 1-9 hours to obtain the catalyst Cu-Zr / SiO2.
5. The preparation method according to claim 4, characterized in that: In the step (1), the soluble salt solution of Cu is one or more of copper nitrate, copper chloride, copper sulfate, copper acetate, and copper acetylacetonate; and the molar ratio of copper to ammonia water is 1:
10.
6. The preparation method according to claim 4, characterized in that: In the step (2), the temperature of the ammonia evaporation process is 80-120 o C; drying temperature is 100-120 o C; calcination temperature is 400-500 o C, the roasting time is 4-6 hours.
7. The preparation method according to claim 4, characterized in that: The soluble salt of Zr is one or more of zirconium nitrate, zirconium chloride, zirconium oxynitrate, zirconium oxychloride and zirconium n-propoxide.
8. Use of the catalyst according to any one of claims 1 to 3 or the catalyst prepared by the preparation method according to any one of claims 4 to 7 in a one-step process for preparing butadiene from ethanol, characterized in that: The reaction is carried out in a fixed bed reactor at atmospheric pressure, and the reaction space velocity range is WHSV = 0.2-10 h -1 , using at least one of nitrogen, helium and argon as carrier gas, carrier gas space velocity GHSV = 500-50000 h -1 , the reaction temperature is 275-375 o C.
9. The use according to claim 8, characterized in that: The reaction space velocity range is WHSV = 0.5-5 h -1 , carrier gas space velocity GHSV = 2000-20000 h -1 .
Citation Information
Patent Citations
Preparation method and application of catalyst for preparing acetaldehyde through ethanol dehydrogenation
CN114054079A